Quality Analysis in Psychology Research on Human Resource Management in the Manufacturing Industry - Elshifa, Aria; Zulfikri, Agung; Pahrijal, Rival (Westscience Press, 2024)
This bibliometric study explores the quality of research in psychology concerning Human Resource Management (HRM) practices within the manufacturing industry. With a focus on assessing trends, patterns, and gaps in existing literature, the study employs a systematic approach to evaluate the depth and rigor of scholarly inquiry. Through a comprehensive analysis of publication metrics, including citation counts, authorship patterns, and thematic clusters, key insights emerge regarding the state of HRM research in manufacturing. Findings reveal a dynamic landscape characterized by diverse thematic clusters, ranging from the psychological dimensions of HRM to strategic practices and organizational behavior. While certain areas receive significant attention, such as psychology, strategic HRM, and HRM practices, others, including human capital management and industrial relations, are relatively underexplored. This study highlights the importance of addressing methodological inconsistencies and theoretical gaps to advance both theoretical development and practical implications in HRM research within the manufacturing sector.